Refractive outcomes of small incision lenticule extraction with accelerated cross-linking (ReLEx SMILE Xtra) in patients with thin cornea - Soori, Hassan; Doroodgar, Farideh; Niazi, Feizollah; Niazi, Sana; Alinia, Cyrus; Sanginabadi, Azad (Researcher Bulletin of Medical Sciences, 2021)
Objective: To study the safety and clinical outcomes of ReLEx SMILE with accelerated cross-linking in eyes with thin cornea. Materials and Methods: Fifty-four thin cornea with corrected distance visual acuity 20/25 or better, stable refraction of at least 1 year, age 21 years or older, and residual corneal thickness of greater than 400 mm before performing collagen crosslinking were studied. Following the removal of lenticule, 0.25% riboflavin in saline was injected into the interface and allowed to diffuse for 60 seconds. Finally, eye was exposed to UV-A radiation of 45mW/cm2 for 75 seconds through the cap. Total energy delivered was 3.4 J/cm2. Results: 54 eyes of 27 patients with mean age of 25.22 ± 2.67 years were treated. Mean follow-up was 6 months. Mean spherical equivalent (SE) was −5.58 ± 1.22D preoperatively and -0.111 ± 0.636D postoperatively. The mean central corneal thickness (CCT) and keratometry changed from 498.39 ± 11.79 µm to 417.85 ± 12.82 µm and 45.47 ± 0.68 D to 41.13 ± 1.13D, respectively. Mean uncorrected visual acuity (UCVA) was 20/25 or better in all eyes. No eyes lost lines of corrected distant visual acuity (CDVA). There were no complications like haze, keratitis, ectasia, or regression. Conclusion: Based on the initial clinical outcome it appears that SMILE Xtra may be a safe. Although further follow-up and larger samples are needed to fully confirm these findings, the results suggest that combined small-incision lenticule extraction and intrastromal corneal collagen crosslinking (CXL) are a promising treatment option for patients for whom conventional laser refractive surgery is contraindicated.